2020
DOI: 10.1016/j.amjcard.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibitor and Angiotensin II Receptor Blocker Use Among Outpatients Diagnosed With COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a viral pandemic precipitated by the severe acute respiratory syndrome coronavirus 2. Since previous reports suggested that viral entry into cells may involve angiotensin converting enzyme 2, there has been growing concern that angiotensin converting enzyme inhibitor (ACEI) and angiotensin II receptor blocker (ARB) use may exacerbate the disease severity. In this retrospective, single-center US study of adult patients diagnosed with COVID-19, we evaluated the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 10 publications
1
28
0
2
Order By: Relevance
“…While this finding warrants further investigation, we do not believe it justifies a change in clinical practice. The lack of association between ACEI or ARB and COVID-19 severity both in our study and in earlier publications [ 23 , 26 28 ] further supports the notion that prescription of ACEI or ARB should not be discontinued in light of the rapidly changing pandemic.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While this finding warrants further investigation, we do not believe it justifies a change in clinical practice. The lack of association between ACEI or ARB and COVID-19 severity both in our study and in earlier publications [ 23 , 26 28 ] further supports the notion that prescription of ACEI or ARB should not be discontinued in light of the rapidly changing pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…We used a four-level COVID-19 severity measure and did not observe a consistent association between the use of either ACEI or ARB and disease severity. A previous study of 590 COVID-19 patients (78 ACEI/ARB users vs. 512 non-users) from a single center did not reveal any significant association between ACEI/ARB use and hospitalization, ICU admissions, mechanical ventilation, length of hospital stay, use of inotropes, or all-cause mortality [ 26 ]. A multi-center study of 338 patients yielded similar results: no significant associations between ACEI/ARB use and hospitalization, ICU admission, mechanical ventilation, or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent months, several clinical studies have reported that the use of ARBs and ACE-Inhs. does not affect disease progression and mortality rates in COVID-19 patients ( Anzola et al, 2020 ; Bae et al, 2020 ; Braude et al, 2020 ; Cordeanu et al, 2020 ; H. Cui et al, 2020 ; Di Castelnuovo et al, 2020 ; Gormez et al, 2020 ; Hippisley-Cox et al, 2020 ; Kalra et al, 2020 ; Khan et al, 2020 , Kim et al, 2020 ; Kocayigit et al, 2020 ; Lafaurie et al, 2020 ; J. Lee et al, 2020 ; Sardu et al, 2020 ; Soleimani et al, 2020 , Taher et al, 2020 ; Trifirò et al, 2020 , Wang et al, 2020 ). Altogether, these results indicate that the use of ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 95%
“…Unfortunately, in latest guidelines by both the WHO and National Institutes of Health (NIH), the above discussed agents are all recommended not to be administered outside of the context of clinical trials [ 41 - 42 ] . Other agents targeting angiotensin-converting enzyme 2 (ACE2) receptor system [ 43 ] or lipid metabolism [ 44 ] are in even more preliminary exploration stage. We are likely still only in the beginning of our battle with SARS-CoV-2.…”
Section: Vaccinementioning
confidence: 99%